Linux device drivers - Rubini, Alessandro (O'Reilly & Associates, Inc., 1998)
This book is for anyone who wants to support computer peripherals under the Linux operating system or who wants to develop new hardware and run it under Linux. Linux is the fastest-growing segment of the UNIX market and is winning over enthusiastic adherents in many application areas. This book reveals information that heretofore has been passed by word-of-mouth or in cryptic source code comments, showing how to write a driver for a wide range of devices.You don't have to be a kernel hacker to understand and enjoy this book; all you need is an understanding of C and some background in UNIX system calls. Drivers for character devices, block devices, and network interfaces are all described in step-by-step form and are illustrated with full-featured examples that show driver design issues, which can be executed without special hardware.For those who are curious about how an operating system does its job, this book provides insights into address spaces, asynchronous events, and I/O.Portability is a major concern in the text.